(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
Venetic is an Indo-European language, attested by more than 500 inscriptions, mostly coming from the modern Italian regions of Veneto and Friuli-Venezia Giulia, and also from Austria and Slovenia, and dating from the 6th century BC to the 1nd century BC. The writing system is an epichoric alphabet, derived from an Etruscan alphabet. The Venetic corpus includes funerary, votives and public inscriptions. Onomastics (personal names; male and female onomastic formula) is well documented. Due to the fragmentary attestation of Venetic, linguistic structures (phonology, morphology, syntax, lexicon) are not well known. There are some problems with classification, but belonging of Venetic to the Italic branch is now accepted.